2010
DOI: 10.1002/marc.200900784
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Poly(dimethylsiloxane) Copolymers with TPE‐Properties via CuAAC (Click Chemistry)

Abstract: Poly(dimethylsiloxane) copolymers were synthesized directly from AA/BB monomers employing a CuAAC reaction (click chemistry) in a polyaddition approach. Using organic dialkynes and oligo(siloxane)s end-functionalized with azide moieties it was possible to obtain siloxane-based copolymers with TPE properties by click chemistry for the first time. As seen from DSC experiments, properties were strongly dependent on the incorporated organic comonomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…[9][10][11][12] Click chemistry has previously been demonstrated to be successful for functionalization of polymers in general polysiloxanes in particular. [16][17][18][19] The azide group on the crosslinker therefore enables reactions with various types of alkyne functional molecules and thereby signicantly widens the functionality that can be introduced into PDMS elastomers. Therefore a number of different functionalities are elaborated.…”
mentioning
confidence: 99%
“…[9][10][11][12] Click chemistry has previously been demonstrated to be successful for functionalization of polymers in general polysiloxanes in particular. [16][17][18][19] The azide group on the crosslinker therefore enables reactions with various types of alkyne functional molecules and thereby signicantly widens the functionality that can be introduced into PDMS elastomers. Therefore a number of different functionalities are elaborated.…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, a detailed study of every intermolecular interaction possible in TPEs has not been performed to date. In a previous communication, our group showed that the CuAAC click reaction can be used for formation of linear polymers based on PDMS . Here, we expand our previous publication and discuss the relationship of monomer structure and polymer properties.…”
Section: Introductionmentioning
confidence: 62%
“…In a previous communication, our group showed that the CuAAC click reaction [ 16 ] can be used for formation of linear polymers based on PDMS. [ 17 ] Here, we expand our previous publication and discuss the relationship of monomer structure and polymer properties. The CuAAC reaction is not susceptible to a lot of functional groups, allowing the introduction of different secondary interactions into the polymer, determined by functionalities and geometry of the incorporated monomers.…”
Section: Introductionmentioning
confidence: 81%
“…The hard block units, responsible for mechanical integrity, provide strong secondary interactions like hydrogen bonds or π–π stacking . The 3D network formed by noncovalent bonds can be disintegrated thermally and thus provides the thermal processability of TPEs.…”
Section: Introductionmentioning
confidence: 99%
“…The hard block units, responsible for mechanical integrity, provide strong secondary interactions like hydrogen bonds [ 13 ] or π-π stacking. [ 14 ] The 3D network formed by noncovalent bonds can be disintegrated thermally and thus provides the thermal processability of TPEs. In TPSEs it is possible to compensate the lack of mechanical stability of siloxanes and to tune the physical properties by inserting only a small amount of self-assembling groups.…”
Section: Introductionmentioning
confidence: 99%